Nutrient Accessibility Influences Stalk Formation in the Benthic Diatom Achnanthidium minutissimum - Pengyu Ji; Adrien Lapointe; Katja Hartenberger; Dieter Spiteller; Peter G. Kroth (Phycology)
Achnanthidium minutissimum is a widely distributed benthic freshwater diatom. The alga can produce stalks that stick the cell to the surface and subsequently extracellular capsules developing into biofilms. Extracts of the diatom-associated bacterium Dyadobacter sp. 32 have been shown previously to induce stalk and capsule formation by the diatom. Here, we studied the impact of macronutrients on the generation of stalks induced by bacterial extracts with respect to the frequency of stalk generation and stalk lengths, using axenic cultures to avoid any additional impact of bacteria on the nutrient availability. We found that nitrate deprivation inhibited cell division of A. minutissimum within four days, but it did not initially affect stalk production or elongation. Silica limitation instead inhibited both stalk production and elongation. Similarly, sulfate was required for stalk formation, which was supported by the energy-dispersive X-ray spectroscopy of A. minutissimum cells showing that sulfur was abundant in the stalks.